The Organizational Design for Automation and Digitalization Initiative using Analytical Hierarchy Process – A Case Study of an Aerospace Manufacturer in Indonesia - Ekawati, Dian; Yudoko, Gatot (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2024)
Abstract. Industry 4.0 become popular when it launched first time in 2011. This revolution refers to interconnection of manufacturing system, which known as Internet of Things. As Indonesia embrace the challenge in 2018, PT SKY, an Indonesia aerospace manufacturing company start the initiative at 2020, by configure digital council. This is to facilitate automation and digitalization initiative within the organization. The team member is part timer from cross function department, who passionate and occupy by self-develop skill on it. Recent challenge of growth of customer demand, and some constraint face by digital council, management view an opportunity to be cost competitive organization company, by develop more focus on automation and digitalization. However, a challenge for company in low-cost country, require proper strategy approach. Based on organization design theory, strategy, and organization structure, have correlation. This study explores the propose organizational design for the company. A decision-making analysis performed thru AHP (Analytic Hierarchy Process) approach to select highest ranking of three alternatives of organization structure, with three criteria. Result analysis show hybrid as highest-ranking score 0.464, then follow by semi structured interview, thematic data analysis, to collect the insight from the team. Based on research execution, the study able to recommends hybrid organization structure with three important actions, to bridge from current digital council ad hoc organization. Keywords: Organization design, manufacturing, AHP, Industry 4.0